Do sex differences in reported weight loss intentions and behaviours persist across demographic characteristics and weight status in youth? A systematic review - Houle-Johnson, Stephanie A; Kakinami, Lisa (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Evidence suggests that young females are more likely to try to lose weight than young males, however whether this sex difference persists across demographic characteristics and weight status is unclear. Further, whether females are more likely than males to try to lose weight using unhealthy weight loss strategies has never been systematically assessed. The objective of this systematic review was to examine the literature on sex differences in weight loss intentions and strategies in children and adolescent observational studies to determine whether sex differences persisted across demographic characteristics (race/ethnicity, grade level) and weight status. Methods Relevant articles published after 1990 were identified using PubMED, Web of Science, and PsycInfo. Searches were conducted in May of 2015 and again in May of 2017. Studies conducted in the US and Canada with participants 18-years old or younger who measured weight loss strategies in the context of weight loss intention were selected. Descriptive statistics were extracted from 19 studies. Results Almost two-thirds of youth reported trying to lose weight. High-school and middle-school aged females reported consistently higher prevalence of weight loss intentions compared to male counterparts, as did Caucasian, African-American, and Hispanic females. The proportion of youth using unhealthy or extreme strategies reached 44 and 13%, respectively, with a similar proportion of males and females endorsing the use of each category of weight loss strategies across studies. Native-American youth reported the highest prevalence (27%) of using extreme strategies. Conclusions Researchers should consider demographic characteristics when reporting prevalence information for weight loss intentions and behaviours, as certain groups might require more targeted public health initiatives. Across characteristics, prevalence ranges were broad for weight loss intentions and use of particular strategies, suggesting the need to standardize and refine data collection and reporting practices in this literature.